Parent-perceived isolation and barriers to psychosocial support: a qualitative study to investigate how peer support might help parents of burn-injured children - Jennifer Heath; Heidi Williamson; Lisa Williams; Diana Harcourt (SAGE Publishing, 2018)
Introduction: Burn injuries can be traumatic and distressing for the affected child and family, with a prolonged period of recovery. This research explores parents' experiences of support following their child's injury and their thoughts on peer support specifically. Methods: Thirteen semi-structured interviews were conducted with parents/caregivers, a mean of three years after their child's injury, either face-to-face or remotely. Responses were analysed using thematic analysis. Results: Analysis produced four themes and 11 sub-themes. These described parents' experiences of loss, change, isolation and access to psychosocial support. This paper focuses on themes of isolation and parents' access to psychosocial support. Discussion: Findings indicate that parents access psychosocial support following their child's injury and often find it helpful; however, there is a prevailing sense of isolation. Parents often seek information online and find that this is lacking. Many parents reported that peer support would be valuable to them, particularly the sharing of experiential knowledge. Conclusion: An online resource may be beneficial for parents, but further research is needed to confirm the exploratory data gained to date, ensuring that any resource developed would meet the identified needs of parents.